Les conflits de compétence entre la Cour Commune de Justice et d’Arbitrage (CCJA) et les Juridictions nationales de cassation des Etats membres de l’espace OHADA - Yaye, Idrissa (Conférence publique organisée Réseau Ivoirien des Juristes d’Affaires (R.I.J.A.F), 2018)
Keywords: CCJA; Compétence; Conflit; Juridiction nationale

L'immunité d'exécution - Mbaye, Mayatta Ndiaye (Matinées de l'ERSUMA, 2017)

Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa - Onyema, Emilia (Rethinking the Role of Courts and Judges in Supporting Arbitration in Africa, 2016)
This second conference in the SOAS Arbitration in Africa Conference series examined how African judges can better support the growth of arbitration. The conference was hosted by the The Lagos Court of Arbitration in their premises in Lagos, Nigeria from 22-24 June 2016. This conference booklet contains some of the papers and slides, and photographs from the conference.
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Courts; Judges; Rôle; Support

The Role of Arbitration Institutions in the Development of Arbitration in Africa - Onyema, Emilia (Arbitration Institutions in Africa Conference, 2015)
This conference which held at the premises of the African Union Commission, Addis Ababa on 23 July 2015 examined the functions of arbitration institutions in Africa. The conferenced discussions focused on sharing experiences by users and providers for the effective administration of arbitration references in the continent. The conference was organised by Dr Emilia Onyema of the School of Law, SOAS. KEY ARTICLES : - Regional Arbitration Institution for ECOWAS: Lessons from OHADA Common Court of Justice and Arbitration ; - The Role of Arbitration Institutions in the Development of Arbitration in Africa ; - “Africa’s Century” – The rise of International Arbitration in Africa and what it means for users of Arbitral Institutions in Africa ; - Reawakening Arbitral Institutions for Development of Arbitration in Africa ; - Opening Up International Arbitration in Africa ; - Africa as a Viable Space for Arbitration: Role of National Courts and Laws - The Role of Counsel in Promoting African Arbitral Institutions ;
Keywords: Africa; Arbitrage; Arbitragem; Arbitration; Conference

Bilateral Investment Treaty between Spain and Guinea: Legal Framework - Vives, Pascual; José, Francisco (2009)
Keywords: Dispute settlement; Equitable treatment; Expropriation; Fair treatment; Guinea foreign investment; ICSID; Investment; Investor; Investor-State Dispute Settlement; National treatment; Spanish BITs